First documented record of the Red-fronted Coot Fulica rufifrons in Ite Wetlands, southern Peru - Vizcarra Romero, Jhonson Klever (2018)
This paper describes and documents the first record of the Red-fronted Coot Fulica rufifrons for Ite Wetlands in Tacna, Peru. An adult individual of this species was observed, on two occasions, in June 2018 in the central part of these wetlands. Apparently, it would be a vagrant individual from Chile.